2009
DOI: 10.1021/jf9012218
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofphytoene synthase1and Carotene DesaturasecrtIGenes Result in an Increase in the Total Carotenoids Content in Transgenic Elite Wheat (Triticum aestivumL.)

Abstract: Dietary micronutrient deficiencies, such as the lack of vitamin A, are a major source of morbidity and mortality worldwide. Carotenoids in food can function as provitamin A in humans, while grains of Chinese elite wheat cultivars generally have low carotenoid contents. To increase the carotenoid contents in common wheat endosperm, transgenic wheat has been generated by expressing the maize y1 gene encoding phytoene synthase driven by a endosperm-specific 1Dx5 promoter in the elite wheat (Triticum aestivum L.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(55 citation statements)
references
References 48 publications
1
52
0
1
Order By: Relevance
“…2): (i) early in the pathway, for the synthesis of phytoene; (ii) for lycopene cyclisation; and (iii) for carotene hydroxylation. Since in wheat the PSY-catalysed reaction has been reported as the rate-limiting step of the biosynthesis pathway, it is feasible that this reaction has a role in the regulation of carotenoid accumulation (Lindgren et al 2003;Cong et al 2009). …”
Section: Carotenoid Biosynthesis and Degradation Pathways And Their Cmentioning
confidence: 99%
“…2): (i) early in the pathway, for the synthesis of phytoene; (ii) for lycopene cyclisation; and (iii) for carotene hydroxylation. Since in wheat the PSY-catalysed reaction has been reported as the rate-limiting step of the biosynthesis pathway, it is feasible that this reaction has a role in the regulation of carotenoid accumulation (Lindgren et al 2003;Cong et al 2009). …”
Section: Carotenoid Biosynthesis and Degradation Pathways And Their Cmentioning
confidence: 99%
“…Golden rice is a glaring example of this promotion (Ye et al, 2000;Paine et al, 2005). Other metabolically manipulated plants for carotenoid improvement are tomato (Fray et al, 1995) canola (Shewmaker et al, 1999), wheat (Cong et al, 2009), potato (Romer and Fraser, 2005), and soybean (Kim et al, 2012). However, knowledge about the role of genes involved in carotenoids biosynthesis for induction of salt tolerance and their expression analyses remained obscure.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, maize would be more important in Sub-Saharan Africa whereas rice and wheat in South Asia at a whole population level, not specifically for children due to data limitation. For transgenic pVA enhancement in crops, identification of the carotenogenesis pathway and its regulating genes in plants and bacteria enabled ectopic expression of specific carotenoids in edible parts of crops [38]. Briefly, carotenogenesis begins with the formation of geranylgeranyl-diphosphate (GGPP) followed by condensation of two GGPPs (Fig.…”
Section: Scientific Progress Of Pro-vitamin a Enhanced Transgenic Cropsmentioning
confidence: 99%
“…Moreover, 94% of wheat currently grown is bread wheat (T. aestivum) which was selected for white flour with little pVA carotenoid [44]. Cong et al (2009) showed bread wheat grains could produce high levels of carotenoids by introducing the maize PSY1 and bacterial carotene desaturases (CrtI) genes [37]. Their transgenic wheat endosperm increased carotenoid contents 10.8 folds compared with the non-transgenic counterpart [37].…”
Section: Development Of Transgenic Pro-vitamin a Enhanced Wheatmentioning
confidence: 99%